PERTUMBUHAN BIBIT MAHKOTA DEWA (Phaleria macrocarpa L.) PADA BERBAGAI KOMPOSISI MEDIA TANAM - Mutmainna, Mutmainna; Sahiri, Nirwan; Adrianton, Adrianton (AGROTEKBIS, 2017)
The study objectives is to determine seedling growth of Gods Crown in polybag. The study design was Randomized Block Design with 6 (six) treatments and 4 (four) replications. Treatment used M0 (control), M1 (1:1:1 (soil:sand:chicken manure), M2 (1:1:2), M3 (1:2:1), M4 (2:1:1), and    M5 (2:1:2). The result of research showed that the M2 (1:1:2 (soil:sand:chicken manure) is tangible effect on plant height and number of leaves, but not give the effect to diameter stem, wet weight     of the canopy, dry weight of the canopy, wet weight of root, dry weight of root and ratio dry of    the canopy and root. Treatment M2 with composition (1:1:2) give the best result at this research. Key Words: Gods Crown (Phaleria macrocarpa L), growth, media growing composition.